Indigenous Philosophies and the "Psychedelic Renaissance". (30th July 2022) - Williams, Keith; Romero, Osiris Sinuhé González; Braunstein, Michelle; Brant, Suzanne
Abstract: The Western world is experiencing a resurgence of interest in the therapeutic potential of psychedelics, most of which are derived from plants or fungi with a history of Indigenous ceremonial use. Recent research has revealed that psychedelic compounds have the potential to address treatment‐resistant depression and anxiety, as well as post‐traumatic stress disorder and addictions. These findings have contributed to the decriminalization of psychedelics in some jurisdictions and their legalization in others. Despite psychedelics' opaque legal status, numerous companies and individuals are profiting from speculative investments with few, if any, benefits accruing to Indigenous Peoples. In this paper, we suggest that the aptly named "psychedelic renaissance, " like the European Renaissance, is made possible by colonial extractivism. We further suggest that Indigenous philosophical traditions offer alternative approaches to reorient the "psychedelic renaissance" towards a more equitable future for Indigenous Peoples, psychedelic medicines, and all our relations.